Scalable uncertainty management : 11th International Conference, SUM 2017, Granada, Spain, October 4-6, 2017, Proceedings /: 11th International Conference, SUM 2017, Granada, Spain, October 4-6, 2017, Proceedings. (2017) - Unknown
No abstract available